2022
DOI: 10.1021/acscatal.2c01596
|View full text |Cite
|
Sign up to set email alerts
|

C–C Bond Forming Reactions Enabled by Vitamin B12─Opportunities and Challenges

Abstract: Cobalt not only is an essential micronutrient for mammals but also marks itself as important in organic synthesis, especially in the field of catalysis. Various useful reactions, such as alkene hydroformylation, hydrogenation, heterofunctionalizations of carbon−carbon double bonds, C−H activation, and crosscoupling reactions, have been realized with the aid of this metal. At the same time, cobalt deserves special attention as a catalyst for radical processes; in fact, in the form of vitamin B 12 , it was desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 86 publications
(138 reference statements)
1
37
0
Order By: Relevance
“…This mode of catalytic polar‐radical hybrid reactivity has also been demonstrated with vitamin B12 derivatives [155,156] . For example, the groups of Gryko and Komeyama have independently reported intermolecular reactions between alkyl tosylates or S‐acyl thiopyridines with electron deficient olefins to give Giese‐type products under blue LEDs irradiation (Scheme 35).…”
Section: Synthetic Uses Of Lmct Reactivity In Organic Synthesismentioning
confidence: 79%
See 3 more Smart Citations
“…This mode of catalytic polar‐radical hybrid reactivity has also been demonstrated with vitamin B12 derivatives [155,156] . For example, the groups of Gryko and Komeyama have independently reported intermolecular reactions between alkyl tosylates or S‐acyl thiopyridines with electron deficient olefins to give Giese‐type products under blue LEDs irradiation (Scheme 35).…”
Section: Synthetic Uses Of Lmct Reactivity In Organic Synthesismentioning
confidence: 79%
“…Although other related photoinduced reactions such as decarboxylation [150,151] have been know at a fundamental level for decades, the synthetic applications of photochemical processes in Co(III) have been largely dominated by the facile C−Co homolysis upon LMCT excited‐states population [152–154] at vitamin B12‐derivatives and bis(dimethylglyoximato) complexes, also known as cobaloximes (Scheme 31A). In this section there are summarized some of the most representative examples to provide a general vision of the field, however for a more comprehensive analysis the reader is referred to any of the excellent reviews on these types of catalysts that are reported elsewhere [155–159] . The general reactivity profile of these compounds under photocatalytic conditions is depicted in Scheme 31B [153] .…”
Section: Synthetic Uses Of Lmct Reactivity In Organic Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Baran et al demonstrated electroreductive generation of Co III –H in the context of alkyne hydrogenation, alkene isomerization, and related transformations . Nevertheless, the exploration of such strategies in synthetic contexts remains rare beyond these examples . In this work, we employed analytical and synthetic tools to study a family of electronically distinct Co­(salen) complexes and obtained qualitative and quantitative insights into the electroreductive generation of Co III –H and its reaction with alkenes (Scheme A).…”
mentioning
confidence: 99%